Trastorno de ansiedad social: aproximación a un caso clínico desde el enfoque cognitivo conductual - Torres Amaya, Josselyn Suggeidy (My University, 2020)
Social anxiety disorder manifests itself in people who perceive their social environment as threatening, causing them fear and discomfort. The main characteristic of this disorder is the sudden and perennial fear of experiencing shame and humiliation within a social interaction. The aim of the present research is to characterize social anxiety disorder from the analysis of a clinical case for the indication of a cognitive-behavioral intervention plan. The study was carried out based on the analysis of a documented case and the review of updated bibliography. The case in question deals with a 14 years old patient who presented problems with sphincter control and neglect of personal hygiene, which was noticed by her classmates and teachers, becoming the cause of constant criticism and mockery, causing difficulty in her interpersonal relationships and sustained thoughts of being abandoned, not accepted or love. Different studies indicate that psychotherapy with cognitive-behavioral approach is by clinical relevance the most used to address social anxiety disorder, allowing the patient to identify his own interpretations about the threatening situation, so that he understands and accepts it; it operates through the modification of thoughts, behaviors and emotions that cause discomfort about his state of mind, in order to improve his performance in daily activities, both at social, family, educational and work levels. From the various techniques such as: psychoeducation, relaxation training, conflict resolution, cognitive restructuring and different types of exposure techniques.
El trastorno de ansiedad social se manifiesta en personas que perciben su entorno social como amenazador, provocándoles miedo e incomodidad. La característica principal de este trastorno es el miedo súbito y perenne a experimentar vergüenza y humillación dentro de una interacción social. El objetivo de la presente investigación es caracterizar el trastorno de ansiedad social a partir del análisis de un caso clínico para el señalamiento de un plan de intervención de tipo cognitivo conductual. El estudio fue realizado a partir del análisis de un caso documentado y la revisión bibliografía actualizada. El caso en mención trata de una paciente de 14 años que presentó problemas con el control de esfínteres y descuido en higiene personal, lo que fue notado por sus compañeros y profesores, volviéndose motivo de constantes críticas y burlas, provocando dificultad en sus relaciones interpersonales y pensamientos sostenidos de ser abandonada, no aceptada o querida. Diferentes estudios indican que la psicoterapia con enfoque cognitivo conductual es por relevancia clínica la más utilizada para abordar el trastorno de ansiedad social, permitiendo al paciente identificar sus propias interpretaciones sobre la situación amenazante, para que lo comprenda y acepte; opera a través de la modificación de pensamientos, conductas y emociones que causan malestar sobre su estado anímico, con el fin de mejorar su desenvolvimiento en las actividades diarias, tanto a nivel social, familiar, educativo y laboral. A partir de las diversas técnicas tales como: psicoeducación, entrenamiento en relajación, solución de conflictos, reestructuración cognitiva y diferentes tipos de técnicas de exposición.
Keywords: ANSIEDAD SOCIAL; ADOLESCENTE; ABORDAJE; COGNITIVO CONDUCTUAL